122 Review of MND patients known to the Specialist palliative care team to improve service provision. (14th March 2023) - Bowen, Joanne; Hall, Kate; Reynolds, Jane
Abstract : Introduction: Dudley Group NHS Trust provides support to patients with a diagnosis of Motor Neurone Disease, working in conjunction with the Regional Specialist Motor Neurone Disease service based at University Hospital's Birmingham and Primary Care Serivces. Care is provided by the Specialist Palliative Care (SPC) department, Dudley Rehabilitation Service, Community Dietitians, Speech and Language services, and District Nursing. Currently all patients are discussed in a bi-monthly MDT meeting attended by the MND CNS (from UHB) and health professionals from the SPC team, Dietician and Speech and Language Therapist. A review of MND patients known to the specialist palliative care team to see if any themes was carried out. Method: Using a proforma a review of patients known to the Specialist Palliative team on the 5.4.22 and deaths during 2022 was carried out using Somerset where MDT and visits are recorded. Results: Eighteen patients known to the specialist palliative care team during this period, 12 male and 6 female. Of the 18 patients 10 died during the review period (Jan – July 2022) with 6 dying at home and 4 in hospital. With regards to the hospital deaths 2 had no DNACPR or ACP in community and this was completed in hospital. Advance care planning discussions were documented for 9 of the patients. There was documentation that some of the patients were GSF blue and therefore, not commenced yet, however, for a number there was documentation that ACP discussions had been challenging. DNACPR in place for 11 of the 18, however for 3 of these were completed in hospital. Discussion: This review has provided useful information regarding the challenge of Advance care planning and that 40% of deaths occurred in hospital. Next steps are to agree standards for referral, discharge and min review when on the caseload and who should be involved including nursing, medical and therapy.